Vitamin D levels and atopic eczema in infancy and early childhood in Norway: a cohort study3. (9th June 2016) - Berents, T.L.; Lødrup Carlsen, K.C.; Mowinckel, P.; Sandvik, L.; Skjerven, H.O.; Rolfsjord, L.B.; Kvenshagen, B.; Hunderi, J.O.G.; Bradley, M.; Lieden, A.; Carlsen, K.‐H.; Thorsby, P.M.; et al.
Summary: Background: Epidemiological data and the effect of sun exposure on atopic eczema (AE) suggest that vitamin D (vitD) may be involved in the pathogenesis. Objectives: To investigate if vitD levels were associated with the presence or severity of AE in the first 2 years of life in children living in south‐east Norway. Methods: Infants, recruited to a clinical trial on acute bronchiolitis ( n = 404) and from the general population ( n = 240), were examined at 1–13 months (first visit) and at 2 years of age (second visit). Caregivers were interviewed using a structured questionnaire. AE was diagnosed clinically, based on well‐established criteria. Disease severity was assessed using the SCORing Atopic Dermatitis index. Blood samples were taken for vitD measurements, using liquid chromatography–tandem mass spectrometry and for common filaggrin mutation analyses. Complete data on AE and vitD were available in 596 and 449 children at the first and second visit, respectively. Results: Atopic eczema was diagnosed in 67 children (11%) at the first visit and in 103 children (23%) at the second. Mean vitD levels were 58·2 nmol L −1 at the first visit and 66·9 nmol L −1 at the second. Using vitD level tertiles in multivariate regression analysis, there was no association between vitD levels and AE at either visit, regardless of filaggrin mutation. In children without AE at the first visit, vitD levels did not predict AE at the second. Conclusions: In this cohort of young children in Norway, we found no association between vitD levels and the presence or severity of AE. Abstract : What's already known about this topic? Epidemiological and clinical data suggest that vitamin D (vitD) may be of importance in atopic eczema (AE). Results from studies on the association between vitD levels and AE are conflicting. What does this study add? In a cohort of young children living in Norway, vitD levels were not associated with AE. Plain language summary available online